Date conversion essentials: The case of Persian to English official translation - Ahmadi Darani (JoSTrans: The Journal of Specialised Translation)
Although ready access to the Internet makes everything easy, if no online date calculator is available, the only solution with official translations is to convert dates by manual calculation. This article examines conversion and interconversion in relation to three kinds of calendar used in official translations in Iran: the Solar, the Lunar and the Gregorian. To this end the article offers a thorough discussion of conceptual (calendarical) knowledge, focusing on the inherent discrepancies existing between these calendars; it then provides further information about manual date calculation, and finally offers information on some useful websites and software.